In Search of Sabrosura and Sabor: possible connections between anthropological methods and performance - Cabanzo, Pilar (Revista Brasileira de Estudos da Presença, 2021)
The goal of this article is to make connections between anthropological methods and performance based on data collected in research about salsa dancing in the city of Rio de Janeiro. The text describes changes in the approach to salsa and focuses on two different dance styles practiced in two ballroom dance schools. The literature on salsa tends to favor its sound structure, leaving aside other sensory stimuli. In contrast, this article presents an ethnographic approach to salsa dancing based on notions of performance. Thus, the purpose is to contribute to dance research from an anthropological perspective.